Maintenance Therapy with Pembrolizumab after Platinum-Doublet Chemotherapy Leading to Hyperprogression in a Patient with Metastatic Bladder Cancer - Yangchun Gu; Huiying He; Mopei Wang (Elsevier, 2021)
The anti-programmed cell death receptor 1 (anti-PD-1) immunotherapy has been recommended in several treatment scenarios of metastatic urothelial cancer (UC), including as a maintenance therapy after first-line chemotherapy. However, the PD-1 inhibitor accelerates tumor growth occasionally, causing hyperprogressive disease (HPD). We presented here a case of HPD in a 43-year-old male Chinese patient with bladder UC, metastasizing to liver and bone, and harboring amplification of Murine Double Minute gene 2, cyclin-dependent kinase 4, fibroblast growth factor receptor substrate 2, ERBB3, and Enhancer of Zeste Homolog 2. After achieving partial remission with the traditional platinum doublet chemotherapy, he sought PD-1 inhibitor (pembrolizumab) for maintenance therapy in another hospital. After 3 doses of pembrolizumab in <2 months, his liver metastasis dramatically increased both in size and number. Liver biopsy confirmed genuine progression. He died from liver failure 6 months later. This case alerted us about HPD again in the scenario of maintenance therapy, enhanced the importance of selecting appropriate patients.